Age-Related Differential Structural and Transcriptomic Responses in the Hypertensive Heart - Marques, Francine Z.; Chu, Po-Yin; Ziemann, Mark; Kaspi, Antony; Kiriazis, Helen; Du, Xiao-Jun; El-Osta, Assam; Kaye, David M. (Frontiers in Physiology, 2018)
While ageing is a critical risk factor for heart failure, it remains uncertain whether the ageing heart responds differentially to a hypertensive stimuli. Here we investigated phenotypic and transcriptomic differences between the young and ageing heart using a mineralocorticoid-excess model of hypertension. Ten-week (‘young’) and 36-week (‘ageing’) mice underwent a unilateral uninephrectomy with deoxycorticosterone (DOCA) pellet implantation (n=6-8/group) and were followed for 6 weeks. Cardiac structure and function, blood pressure and the cardiac transcriptome were subsequently examined. Young and ageing DOCA mice had high blood pressure, increased cardiac mass, cardiac hypertrophy and fibrosis. Left ventricular end-diastolic pressure (LVEDP) increased in ageing DOCA-treated mice in contrast to young DOCA mice. Interstitial and perivascular fibrosis occurred in response to DOCA, but perivascular fibrosis was greater in ageing mice. Transcriptomic analysis showed that young mice had features of higher oxidative stress, likely due to activation of the respiratory electron transport chain. In contrast, ageing mice showed up-regulation of collagen formation in association with activation of innate immunity together with markers of inflammation including cytokine and platelet signalling. In comparison to younger mice, ageing mice demonstrated different phenotypic and molecular responses to hypertensive stress. These findings have potential implications for the pathogenesis of age-related forms of cardiovascular disease, particularly heart failure.